ANALYZING FUTURE BUSINESS BASED ON SWOT ANALYSIS (Eureka Journal of Business, Economics & Innovation Studies, 2026)
In the context of increasing market uncertainty and rapid technological change, strategic planning plays a crucial role in ensuring sustainable business development. This paper analyzes future business prospects based on the SWOT analysis framework, which evaluates internal strengths and weaknesses alongside external opportunities and threats. The study aims to identify key strategic factors that influence long-term business performance and competitiveness. Using qualitative and analytical methods, the research examines how SWOT analysis can support decision-making, risk management, and strategic forecasting in modern business environments. The results demonstrate that systematic SWOT-based analysis enables organizations to anticipate future challenges, leverage potential opportunities, and align internal capabilities with external market conditions. The findings highlight the practical relevance of SWOT analysis as an effective strategic tool for future-oriented business planning and managerial decision-making.
Keywords: SWOT analysis; strategic planning; future business analysis; business forecasting; competitive advantage; decision-making.